Mitochondrion‐Specific Live‐Cell Bioprobe Operated in a Fluorescence Turn‐On Manner and a Well‐Designed Photoactivatable Mechanism. (7th October 2015) - Gu, Xinggui; Zhao, Engui; Lam, Jacky W. Y.; Peng, Qian; Xie, Yujun; Zhang, Yilin; Wong, Kam Sing; Sung, Herman H. Y.; Williams, Ian D.; Tang, Ben Zhong
Abstract : A novel mitochondrion‐specific live‐cell fluorescence turn‐on photoactivatable bioprobe, named o ‐TPP3M, is designed and readily prepared, operating in a new photoactivatable mechanism based on a twisted intramolecular charge‐transfer effect, the restriction of intramolecular rotations, and photocyclodehydrogenation. This bioprobe exhibits unique photoactivation behavior, a large signal‐to‐background ratio, and no cytotoxicity to living cells, providing a promising candidate for varied bioresearch.